Are You Sure You Want to View This Community? Exploring the Ethics of Reddit's Quarantine Practice. Issue 4 (1st October 2020) - Carlson, Caitlin Ring; Cousineau, Luc S.
ABSTRACT: In the United States, social media organizations are not legally liable for what users do or say on their platforms and are free to regulate expression in any way they see fit. As a result, dark corners of the Internet have emerged to foster communities whose sole purpose is to create and share content that subjugates members of traditionally marginalized groups. The subreddit, /r/TheRedPill, is one such community. This article explores whether hiding this offensive content through digital "quarantine" or removing the community altogether is more ethically justifiable. We draw on theorizing about the ethics of social media content moderation to develop a framework for ethical decision-making based on transparency, corporate social responsibility, and human dignity to guide decisions about content removal. Using/r/TheRedPill as a case study, we argue that the most ethically justified course of action is for Reddit to remove the site entirely from its platform.